HTML5 package media: How does it affect elementary school students’ concept understanding and self-efficacy? - Rahman, Arief Aulia; Sanda, Elsa Alvionita; Refugio, Craig N; Zulnaidi, Hutkemri (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Background: HTML5 Package media, equipped with features and displays, provides a clearer visual display in learning geometry compared to traditional lecture-based teaching. This approach facilitates students in observing and understanding geometry concepts, positively impacting their self-efficacy.Aim: The study aims to assess the impact of HTML5 packages on students' understanding of geometry concepts and their self-efficacy.Method: The research, a quasi-experimental study, used simple random sampling to select 63 students. Data were collected through tests and questionnaires, and the analysis was conducted using MANOVA.Result: The findings reveal a significant effect of the HTML5 Package on both concept understanding and self-efficacy. The experimental group scored higher than the conventional group, with significant values in Pilae Trace, Wilk Lambda, Hotelling Trace, and Roy's Largest Root analyses.Conclusion: The HTML5 Package media effectively enhances the understanding of geometry concepts and self-efficacy among students. While the effect size is modest, it is notably better than conventional learning methods. The study suggests broader application and research involving more students and diverse mathematical topics could yield more influential results.